Urgency of Cryptocurrency Regulation in Indonesia: The Preventive Action for Ransomware Crime - Winnie Stevani; Hari Sutra Disemadi (Fakultas Hukum Universitas Hang Tuah, 2021)
Disruption is a double-edged sword since, in addition to facilitating digitization, it also serves as a target for cybercriminals to conduct their schemes. Cryptocurrency is a type of virtual currency that uses cryptography technology to enable digital transactions in cyberspace. Ransomware is one type of crypto crime that has increased in 2020 occurrences. More over, ransomware is a way for cybercriminals to make money by threatening victims with access limitations, data deletion, and data dissemination in exchange for a ransom payment. Furthermore, the government hasn't provided recognition and protection for its inhabitants, the creation of a legal vacuum (rechtsvacuum) in Indonesia surrounding cryptocurrency regulation is seen to be damaging to digital users. In light of these issues, the goal of this research is to assist the Indonesian authorities in comprehending the fundamental issues surrounding crypto crimes such as ransomware. Then, to assess the prospects of cryptocurrency as a virtual currency in Indonesia, the research technique employed is a normative juridical research method with a conceptual approach and law. This paper demonstrates that the crime of ransomware will hinder cyber law enforcement in Indonesia, resulting in a detrimental impact on economic development and vulnerability to cyberattacks that harm national security. As a result, if cryptocurrency stays in a legal void or ‘gray area’, governments must be aware and prioritize preventive actions against ransomware attacks and their consequences. This preventative step could take the form of regulating cryptocurrency in Indonesia as virtual money and block ransomware activity.